An assessment of financial catastrophe and impoverishment from out-of-pocket health care payments in Swaziland - Cebisile Ngcamphalala; John E. Ataguba (Taylor & Francis Group, 2018)
Background: As the drive towards universal coverage is gaining momentum globally, the need for assessing levels of financial health protection in countries, particularity the developing world, has increasingly become important. In Swaziland, the level of financial health protection is not clearly understood. Objective: To assess financial catastrophe and impoverishment from out-of-pocket payments for health services in Swaziland. Methods: The nationally representative Swaziland Household Income and Expenditure Survey (2009/2010) dataset is used for the analyses. Data are collected by the Central Statistics Office in Swaziland. The final dataset contains information on 3,167 households (i.e. about 14,145 individuals) out of the anticipated 3,750 households. Financial catastrophe is assessed using an initial threshold that is adjusted to increase with household income (i.e. rank-dependent). Payment for health services is considered catastrophic when they exceed the threshold. Impoverishment is assessed using a national poverty line and an international poverty line ($1.25/day). Results: Using an initial threshold of 10.0% of household expenditure, 9.7% of Swazi households experience financial catastrophe while the proportion is estimated at 2.7% using an initial threshold of 40.0% of non-food expenditure. Between 1.0% and 1.6% of the Swazi population, representing between 10,000 and 16,000 people are pushed below the poverty line because of out-of-pocket payments. These findings indicate that financial health protection is not adequate in Swaziland. Conclusion: If Swaziland is to move towards achieving universal health coverage, there is a need to address the burden created by direct out-of-pocket payments. Among other things, this means that the country needs to consider financing mechanisms that guarantee equitable access to needed quality health services, which do not place undue hardship on the poor and vulnerable.